The research and application on highlight line of curved surface quality evaluation based on 3D assembly environment - Qi Gu; Nengjun Ben; Weidong Hui; Chao Wang; Mingxin Huang (КНУБА, 2018)
In view of the present situation of quality analysis methods of curves and curved surfaces, the paper introduced the theoretical basis and mathematical expression of curves and curved surfaces. Four highlight line configuration types, such as reflection, projection, isocline, reflection contours, for evaluate the curves and curved surface quality had been studied in the 3D assembly environment. Finally, a comparative analysis of impeller base surface has been given by the four typesin a 3D impeller assembly.
Keywords: assembly environment; curved surface quality; highlight line analysis; 514.18